Motor errors compensating adaptive control model in exercise kinematics - Zagrevskiy, V. I.; Zagrevskiy, O. I. (Theory and Practice of Physical Culture, 2020)
Motor skills are often executed with kinematic deviations from the ideal programmed trajectory that may be referred as the sample technique execution sequence. The article considers a mechanical-mathematic control model to compensate errors in the startup coordinates and secure a right body positioning on the programmed trajectory. Objective of the study was to develop an adaptive control model to drive the movement sequence from the startup phase state to the required final state. We used movement biomechanics methods for the movement structure analysis and biomechanical structuring of exercises; automatic control methods to synthesize the adaptive control mechanism with a feedback capacity; and modeling methods to mimic a movement sequence on a computer. Subject to the study was the adaptive control to secure the movement sequence being guided from the startup phase to the required final phase. The goal was achieved by a computer model of the movement produced by targeted computation experiments. The article overviews the adaptive control building mathematical toolkit and findings of the computation experiments. The study has resulted in the new motor errors compensating adaptive control model designed to guide the controlled subject into the required final phase